In-situ visualization of heavy oil behavior in supercritical water using neutron radiography. (2nd November 2020) - Shoji, Eita; Kikuchi, Takahiro; Yamagiwa, Koshiro; Kubo, Masaki; Tsukada, Takao; Takami, Seiichi; Sugimoto, Katsumi; Ito, Daisuke; Saito, Yasushi
Highlights: Heavy oil behavior in supercritical water was visualized by neutron radiography. The effects of the heavy oil and supercritical water flow rates were presented. The heavy oil behavior changed with the flow rates. Neutron radiography was capable of visualizing heavy oil in supercritical water. Abstract: Supercritical water upgrading of heavy oil has attracted considerable attention, as the upgrading process can reduce the sulfur content and decrease the average molecular weight of the oil. Understanding the flow and mixing behavior of heavy oil in supercritical water is important to improve the process efficiency. We performed neutron radiography experiments to directly visualize the behavior of heavy oil in supercritical water. Atmospheric residue was used as a heavy oil sample, and the heavy oil and supercritical water were supplied countercurrently to a 1/2-inch tube reactor packed with Al2 O3 particles with a diameter of 3 mm; the pressure and temperature were set to 25 MPa and 400°C. The behavior of the heavy oil in the supercritical water depended on the oil and water flow rates. This study demonstrates that neutron radiography is a feasible visualization technique for the investigation of heavy oil behavior in supercritical water.